The Characterization of Impact Dynamics in Aerospace Structures - The Case of Deformable Impactors - Christoforou, Andreas; Yigit, Ahmet S. (My University, 2023)
This paper presents guidelines on the use of a characterization diagram for impact dynamics scaling and damage tolerance studies for aerospace structures. It is demonstrated that the diagram obtained for rigid impactors, can also be used for deformable impactors such as hail and bird strikes. By placing the impact response on the diagram useful information on the type of response and damage can be predicted prior to running experiments or simulations. It is expected that this methodology could be a very powerful tool to designers and experimentalists who work in the area of design and commissioning for damage resistance and tolerance especially with composite structures.
Keywords: composite structures; damage; impact dynamics; impact testing; scaling